Lighting Design for Visual Comfort and Energy Efficiency Considerations: A Patient Room Case Study - Samaneh Aghajari; Cheng-Chen Chen (International Journal of Engineering and Technology Innovation, 2025)
Discomfort glare causes unease and distraction, significantly affecting patients, staff, and visitors. Achieving visual comfort is essential for glare reduction, as it is primarily influenced by artificial lighting in the workplace. This study examines the probability of visual comfort and the unified glare rating (UGR) as measures of discomfort glare. UGR calculations compare three types of artificial lighting sources in a hospital patient room, considering both visual comfort and energy efficiency. This study analyzes different lighting installations with a focus on surface properties and their relative height as critical factors for enhancing visuals and reducing energy consumption. The results show that increasing the reflection coefficient can reduce energy consumption while improving visual comfort. Although LED lighting generally outperforms traditional lamps, the latter can still achieve significant performance improvements with increased surface reflectance.